FILSAFAT HUKUM: Aktualisasi Critical Legal Studies Di Indonesia - Gojali, Dudang (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
This paper discusses Critical Legal Studies as a critical study of law that opposes the school of legal formalism. As a critical study, Critical Legal Studies accommodates not only Marxist legal ideas, but also liberal-radical and postmodernism. This paper also discusses the basic criticism of Jürgen Habermas's legal-communication theory towards Critical Legal Studies and then the basic criticism of feminism towards Jürgen Habermas. This paper closes with the thoughts of Carol Smart who updated the argumentation of Critical Legal Studies.